1992
DOI: 10.1002/job.4030130705
|View full text |Cite
|
Sign up to set email alerts
|

Thought self‐leadership: The influence of self‐talk and mental imagery on performance

Abstract: Self-leadership theory can be described as the 'process of influencing oneself as opposed to the influence of leaders over followers (Manz, 1983(Manz, , 1986. We focus on and develop a model for a particular aspect of self-leadershipthought self-leadership ~ emphasizing two primary elements, self-talk and mental imagery. The major thrust of this model is that employees can influence or lead themselves by utilizing specific cognitive strategies that focus on individual self-dialogue and mental imagery. It is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(225 citation statements)
references
References 55 publications
6
216
0
3
Order By: Relevance
“…Because self-leadership is conceptualised as an intrapersonal process for influencing oneself (Manz, 1986;Manz & Neck, 2004;Sahin, 2011), it is not surprising that previous research has shown that each component of selfleadership contributes to performance (Neck & Houghton, 2006). For example, Neck and Manz (1992) found that individuals who received training in the constructive-thought pattern strategies experienced enhanced states of positive affect (enthusiasm) and job satisfaction as well as a decreased state of nervousness relative to those who had not received such training. The behaviour-focused coefficient of 0.104 means that an improvement in behaviour-focused selfleadership by 1.0% will lead to a 10.4% increase in job performance.…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…Because self-leadership is conceptualised as an intrapersonal process for influencing oneself (Manz, 1986;Manz & Neck, 2004;Sahin, 2011), it is not surprising that previous research has shown that each component of selfleadership contributes to performance (Neck & Houghton, 2006). For example, Neck and Manz (1992) found that individuals who received training in the constructive-thought pattern strategies experienced enhanced states of positive affect (enthusiasm) and job satisfaction as well as a decreased state of nervousness relative to those who had not received such training. The behaviour-focused coefficient of 0.104 means that an improvement in behaviour-focused selfleadership by 1.0% will lead to a 10.4% increase in job performance.…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…Constructive thought pattern strategies are often referred to as thought self-leadership. It suggests that individuals can influence and control their own thoughts through the use of specific cognitive strategies designed to facilitate the formation of constructive thought patterns that can positively affect performance (Neck & Manz, 1992). In addition, constructive thought pattern strategies may be particularly useful in increasing team members' self-efficacy beliefs for sharing leadership roles.…”
Section: Cognitive and Behavioral Strategiesmentioning
confidence: 99%
“…These individuals use optimistic thought patterns to create opportunities so that they can better cope with difficulties that may impede them from attaining their desired ends. The nature of an individual's thought pattern affects her or his behaviors and outcomes (Neck and Manz, 1992). Seligman (1991) argued that individuals tend to develop either optimistic or pessimistic thoughts.…”
Section: Introductionmentioning
confidence: 99%